African Folklore in Women's Narratives: An Exploration of Tsitsi Dangarembga's Nervous Conditions - Megbowon, Funmilola (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Many of the contemporary challenges faced by women in Africa are deeply intertwined with African traditions and long-standing cultural practices. However, while African traditions indeed contribute to many of the challenges women face today, they also offer pathways to empowerment. African literature and folklore are posited in this study to be sources of retrospection into these African women-related narratives. This study aims to analyse folklore within a selected African literary text, in relation to women-centred narratives and explore the role of folklore in women’s narrative and experiences. Using Tsitsi Dangarembga's Nervous Conditions as a primary text, this study adopts a textual and interpretative analysis framed by feminist and nativist branches of postcolonial theory to achieve the objectives of the study. The study identifies two folklores (storytelling and marriage rituals) as central to women-related narratives and traditions depicted in the text. The analysis further reveals that African folklore can function as a double-edged sword as either reinforcing women’s subjugation or serving as a vehicle for their empowerment. The continuous integration of folklore in literature serves as a tool for illuminating and preserving previous experiences of women and the traditions of African culture. African folklore is an enabler of women subjugation, but it also has the capacity to challenge patriarchal structures and promote women’s empowerment. Deliberate efforts are required to amplify the women-empowering aspects of folklore. Strategic emphasis that focuses on promoting empowering narratives within folklore, challenging and deconstructing harmful narratives through critical engagement, and cultural revitalization by applying a gender lens to traditional practices are some of the implications for women’s empowerment.